(untitled) (Intercom - Brazilian Journal of Communication Sciences, 2026)
Studies that address the behavior of searching, sharing and using information and knowledge have been one of the main objects of investigation today. There are several new demonstrative, predictive or prescriptive models that present varied perspectives on Information and Knowledge Management. However, there is little research dedicated to comparing the relationships between models to understand disparities or convergences, which represents a gap to be addressed. Given this context, the proposed objective is to compare the adherence between two different theoretical models, both validated by empirical tests that evaluate the processes of identifying needs, searching and using information and knowledge. Regarding the methodology for carrying out this endeavor, a qualitative approach was chosen, using the content analysis technique. As for the results, the models analyzed present particularities of approach and methods, however there are significant convergences. We can conclude that the models developed have a high level of conceptual basis and potential for replicability. Despite the distinctions between the models studied, the alignment of the indicators listed by both is evident and the research leaves a legacy for discussions and expansion of debates with a view to providing new paradigms for understanding phenomena linked to infocommunication issues.